Guiding assessment for learning in Indigenous health at level 9 of the Australian Qualifications Framework : final report. - Delany, Clare; Ewen, Shaun (Australia. Dept of Education and Training (DET), 2018)
This project, 'Guiding Assessment for Learning in Indigenous Health' involved an investigation (using qualitative research methods) of assessment approaches used by academics involved in teaching Indigenous health at the Master's degree level across Australia and in New Zealand. This data was then used to compare current assessment and teaching practices with educational theory and learning goals stipulated by the Australian Qualification Framework (AQF) at Master's level learning. The key project deliverable was a practical teaching resource; A capability approach to assessment for Indigenous health education, to inform and guide effective assessment for learning in Indigenous health (Delany, et al., 2017b). Interview data showed that academics wanted to transform students' perspectives of their role from knowing about Indigenous health as a component of basic health education content, to developing skills to critically and creatively provide health care relevant to the needs and strengths of Indigenous people. In contrast to these complex learning goals, assessment tasks focused on synthesising information about specific historical and sociocultural factors contributing to the health of Indigenous people. The majority of assessment tasks had defined and pre-set parameters leaving relatively little room for students to identify, critique and build on their own understanding and perspectives. This had the effect of rendering the complexity of academics' desired learning goals invisible to students. Participants described a range of factors which either inhibited or assisted them in their role to introduce Indigenous health content in health professional programs. Within the classroom, these included student resistance to Indigenous health content especially if they did not see its' relevance to their future work. Many described feeling uncertain about their expertise to teach Indigenous health (especially if they were not Indigenous themselves). Academics who were Indigenous spoke of feeling responsible for appropriately representing Indigenous knowledge and beliefs. All participants spoke about the importance of having institutional support for this aspect of health program curricula. If students were to take it seriously, it needed to be explicitly valued and meaningfully assessed. [Executive summary, ed]